Scalable, template-free synthesis of conducting polymer microtubes1. Issue 32 (10th April 2015) - Díaz-Orellana, Kryssia P.; Roberts, Mark E.
<x xml:space="preserve">Abstract</x> A template-free synthesis method is used to create polypyrrole microtubes on stainless steel mesh substrates. The physical and electrochemical properties of the microtubes can be tailored by changing substrate dimensions and growth conditions.